2009
DOI: 10.1039/b817991c
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure imidazolinium-dithiocarboxylates as highly selective novel organocatalysts

Abstract: Asymmetric imidazolinium-dithiocarboxylates have been found for the first time to be highly selective catalysts; in the present case, the novel organocatalysts were able to catalyze the Staudinger reaction in up to 96% ee and 99% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…[23] Chiral enantiopure versions of these organocatalysts were subsequently applied to the asymmetric synthesis of β-lactams by the Staudinger reaction. [24] In view of the rich chemistry exhibited by NHC·CO 2 and NHC·CS 2 betaines, and the marked differences between these two types of compounds, we launched a program to investigate the structural properties and reactivity of the related NHC·COS zwitterions. To the best of our knowledge, such adducts have never been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Chiral enantiopure versions of these organocatalysts were subsequently applied to the asymmetric synthesis of β-lactams by the Staudinger reaction. [24] In view of the rich chemistry exhibited by NHC·CO 2 and NHC·CS 2 betaines, and the marked differences between these two types of compounds, we launched a program to investigate the structural properties and reactivity of the related NHC·COS zwitterions. To the best of our knowledge, such adducts have never been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…An enantioselective Staudinger reaction of ketene 174 and imine 173 with imidazolinium-dithiocarboxylate catalyst (175) was developed by Wilhelm, et al, Scheme 3.55 [71].…”
Section: [2 + 2] Cycloadditionsmentioning
confidence: 99%
“…6 The more Lewis basic nature of imidazolium dithiocarboxylates has allowed them to be used successfully as catalysts for the cyanosilylation of aldehydes, 7 and in the Staudinger reaction to prepare β-lactams. 8 Delaude demonstrated that the NHC·CS 2 can also be used as ligand and coordinates as a κ 2 ,S,S′ chelate to the Ru II centre in the first examples of transition-metal complexes with such ligands (B in Chart 1). His experiments also demonstrated the greater stability of the NHC·CS 2 than NHC·CO 2 betaines towards CE 2 loss.…”
mentioning
confidence: 99%